Time Perspective in Patients with Affective Disorders: Review of Scientific Research - Anna Yu Zakharova; Anna V Trusova (Peoples' Friendship University of Russia (RUDN University), 2019)
The article presents the results of the theoretical analysis of the Russian and international studies devoted to the phenomenon of the time perspective of the personality. The time perspective is an extremely relevant research topic, and at the same time, a littlestudied area of psychological and psychiatric science. The history of the term is brieﬂy described, the main approaches to the deﬁnition of the concept are considered, the important properties and characteristics of the time perspective of the individual are determined. In this article, the features of the time perspective of a personality are considered with regard to anxiety and depression, important manifestations of aﬀective disorders; the properties of the temporal perspective are considered in the context of manifestations of anxiety and depression in patients with aﬀective disorders. The connection of the depressive episodes and the subjective attitude to the past, present, and future is marked, the role of dysfunctional time perspective in the context of depressive and anxious experiences is emphasized. The inﬂuence of subjective perception of time, especially future, on the increasing anxiety is reﬂected. Some foreign and domestic studies of the time perspective in patients with aﬀective disorders are considered and analyzed. We found some diﬀerences in subjective perception of time and time perspective in patients with anxious and depressive manifestations: the speed of time in depressed patients is slowed down, in anxious patients it is accelerated; as for the attitude to the past, present, and future, in patients with severe depressive manifestations there is a pessimistic attitude to the events of the future and ﬁxation on the events of the past.